Effects of angular leaf spot and rust on plant growth and yield of Phaseolus vulgaris - Jesus Junior, Waldir Cintra de (2001)
The main purpose of the thesis was to understand the effects of angular leaf spot (Phaeoisariopsis griseola) and rust (Uromyces appendiculatus) on the variables related to plant growth and yield of common bean (Phaseolus vulgaris). This thesis was organized in to five chapters. In the first two chapters data from three field experiments were analyzed using different approaches. The last three chapters referred to independent experiments. Chapter 1. The effects of angular leaf spot and rust, separately or combined, on host growth (expressed as area under leaf area progress curve - AULAPC, healthy leaf area duration - HAD, and healthy leaf area absorption - HAA) and yield of individual bean plants were investigated. All inoculated treatments had significantly more severe disease and less yield than the control treatment. In general, yield was not related to disease severity or area under disease progress curve. In contrast, the highest yields were always related to the highest values of HAD, and HAA. The relationship between yield and HAD, and HAA was linear. It was concluded that angular leaf spot reduced the leaf area because of defoliation while rust did not affect the leaf area. Rust reduced yield more than four times that of angular leaf spot, although the decrease in photosynthesis to angular leaf spot was twice that of rust. Chapter 2. The effect of angular leaf spot and rust, separately or combined, on leaf gas exchange (net photosynthetc rate, stomatal conductance, and transpiration) of common bean was reported. The inoculation of plants with P. griseola (P), U. appendiculatus (U), and a combination of the two pathogens (P+U) caused a significant reduction in the net photosynthetic rate and yield. Treatments P and P+U resulted in a significant reduction of stomatal conductance. The interactive effects of the pathogens on yield could be explained in part by the decreases in stomatal conductance and in the net photosynthetic rate of diseased bean leaves. Chapter 3. The relationships among angular leaf spot, healthy leaf area, effective leaf area, and pod yield of common bean were evaluated. Visual and virtual severity, and area under disease progress curve (AUDPC) showed no correlation with pod yield. However, healthy leaf area duration (HAD), healthy leaf area absorption (HAA), effective leaf area duration (ELAD), and effective leaf area absorption (ELAA) were significantly correlated with pod yield. The relationships between yield and HAD, HAA, ELAD, and ELAA were linear in each of the three trials. The slope of the yield-healthy leaf area index (HLAI) relationship proved to be stable, regardless of planting date and bean growth stage (from R6 to R8). HLAI is proposed as a key explanatory variable for a transportable system of disease management; it may be useful in producing precise recommendations at the farm level. Chapter 4. The strategies to manage angular leaf spot on common bean based in molybdenum application and chemical control were studied. It was observed that the molybdenum treatments showed smaller severity of angular leaf spot, and higher leaf area, net photosynthetic rate and yield, than the treatments that had no Mo. To control angular leaf spot, it was important to spray fungicide once or twice during the flowering period, which takes place ca. 25 to 45 days after planting. Chapter 5. The applicability of the equipment LAI-2000 (Li-Cor) to estimate leaf area index (LAI) was tested. It was concluded that the equipment could be used to estimate LAI on common bean.